Role of platelet-activating factor in Chinese hamster ovary cell responses to cholera toxin. - Thielman, N M (1997)
Cholera toxin (CT)-induced intestinal secretion and Chinese hamster ovary cell (CHO) elongation involves cyclic adenosine monophosphate and protein synthesis-dependent prostaglandin formation. We previously reported inhibition of CT-induced intestinal secretion and CHO elongation by platelet-activating factor (PAF) receptor antagonists and secretion of PAF by human intestinal epithelial cells exposed to CT. Herein, we show that PAF is involved after cAMP and that PAF, like CT, mediates prostaglandin E2 synthesis in CHO cells. CT-induced CHO elongation was blocked by specific PAF receptor antagonists, BN52021 and SR27417. SR27417 blocked dibutyryl cAMP-induced CHO elongation, but did not alter CHO elongation caused by PGE2. Neither CT-stimulated cAMP accumulation nor PGE2 production was inhibited by SR27417. Both PGE2 and PAF caused significant CHO elongation, but the latter did not stimulate significant cAMP production. In addition, PAF, like CT and dibutyryl cAMP, stimulated significant PGE2 production. Finally, the protein synthesis inhibitor cycloheximide, which completely blocks the effect of CT on prostaglandin synthesis, also blocked that of PAF, suggesting that PAF also mediates protein synthesis-dependent prostaglandin formation. We conclude that PAF is involved in CHO cytoskeletal responses to CT after the accumulation of cAMP and, like CT, PAF stimulates protein synthesis-dependent prostaglandin accumulation.